2015
DOI: 10.1017/jfm.2015.669
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of a near-motion-trapped mode: free motion in heave with negligible radiation

Abstract: A simple geometry which exhibits near-motion-trapping is tested experimentally, along with perturbed versions of the structure. The motion of the freely floating structure and the surrounding wave field is tracked and the near-motion-trapped mode is found, characterised by a slowly decaying heave motion with very small linear radiation of energy. It is found that the latter property is a better discriminator of the perturbed geometries as viscous damping masks fine differences in radiation damping as far the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
3
3
0
Order By: Relevance
“…We associate this damping with linear wave radiation outwards and generated by machine motion in otherwise still water. Even for a rotation angle of 25 • , there seems to be little viscous damping -an observation supported by a heaving ring of eight similarly sized cylinders recently reported by Wolgamot et al (2016) with oscillation periods close to 1 sec.…”
Section: The Damping Behavioursupporting
confidence: 54%
“…We associate this damping with linear wave radiation outwards and generated by machine motion in otherwise still water. Even for a rotation angle of 25 • , there seems to be little viscous damping -an observation supported by a heaving ring of eight similarly sized cylinders recently reported by Wolgamot et al (2016) with oscillation periods close to 1 sec.…”
Section: The Damping Behavioursupporting
confidence: 54%
“…Stratigaki et al [23] presented their experimental study of a 25-WEC array. Similar experimental studies were conducted by Rahm et al [24], da Fonseca et al [25], Wolgamot et al [26], and Ruiz et al [27]. However, studying interaction effects through experiments has two major drawbacks.…”
Section: Introductionsupporting
confidence: 54%
“…An array of 50 truncated cylinders was studied in regular waves by [388], and it was found that resonance modes were present, although they were smaller than those predicted by numerical simulations. Trapped and neartrapped modes were also observed within an array of eight fixed truncated cylinders [838], and in short-crested waves [376].…”
Section: Experimental Modellingmentioning
confidence: 90%